Effect of GnRH on Embryo Recovery and Quality in Crossbred Sahiwal Cows - SIDDIQUl, M U; PANCHAL, M T; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
Effect of GnRH on embryo recovery and quality in crossbred Sahiwal cows was studied in 12crossbred (HF x Sahiwal) cows divided in two groups (Group A: 6 cows without GnRH and Group B: 6cows with GnRH). For induction of superovulation, FSH-P (Folltropin-V, Bioniche Animal Health,Canada, @ 200 mg per donor in 8 equally divided doses of 1.25 ml each) was administered by i.m. routeover 4 days at 12 hr interval, starting day 9 -11 post estrus. A single dose of PGF2a (Iliren, lntervet, @ 5ml) was given i.m. 48 hr after the first FSH injection, to bring the donor in heat. First Al was done 48 hrafter PG injection, followed by two more inseminations at 12 hr intervals. A dose of2.5 ml Receptal (10.5μg Buserelin Acetate, GnRH Analogue, lntervet International, GmbH, Germany) was given i.m. to cows ofGroup B only at the time of first Al. On day 7 of first AI, cows were flushed for embryo recovery. Among6 cows (Group A), only 4 (66.67%) responded to FSH treatment with the total number of CL to be 28(7 .00/donor) and a total of 17 (3 viable, 3 degenerated and 11 UFO) embryos. The mean recovery of totaland viable embryos (VE) for responded cows and overall were found to be.4.25 and 0.75 and 2.83 and 0.50embryos per flush, respectively. Among 6 cows (Group B), 5 (83.33%) responded to FSH treatment withthe total number of CL to be 31 (6.20/donor) and a total of 21 (12 viable, 3 degenerated and 6 UFO)embryos. The mean recovery of total and viable embryos for responded cows and overall were found to be4.20 and 2.40 and 3.50 and 2.00 embryos per flush, respectively. There was a significantly higher recoveryof viable embryos in Group B (12 VE; @ 2.0/flush) than of Group A (3 VE; @ 0.5 /flush). The quality ofviable en,bryos recovered from Group B (with GnRH) was higher (83.33% grade A and 16.67% grade B)than Group A (66.67% grade A and 33.33% grade B). It was concluded that injecting GnRH at the time ofAl in superovulated cows is helpful in increasing the fertilization rate and recovery of more viable embryosof superior quality.
Keywords: GnRH; Embryo recovery; Crossbred Sahiwal cows